SERS of Trititanate Nanotubes: Selective Enhancement of Catechol Compounds. Issue 28 (30th July 2018) - Liu, Ruochen; Morris, Edmund; Cheng, Xiaorong; Amigues, Eric; Lau, Kim; Kim, Baekman; Liu, Yuanhang; Ke, Zhipeng; Ashbrook, Sharon E.; Bühl, Michael; Dawson, Graham
Abstract: The surface enhanced Raman scattering of trititanate nanotubes (TiNT) modified with enediol ligands was investigated and it was found that the functional group dramatically affects the enhancement observed. For TiNT‐4‐nitrocatechol, a SERS enhancement is seen; however, when dopamine is attached, no signal is seen. The relative band gap positions upon 785 nm laser excitation are proposed to explain the observed phenomenon. This attachment is investigated by solid state NMR and UV/Vis spectroscopy and supported by DFT calculations to offers further insights into catechol coatings of nanomaterials and SERS by the chemical method. We expect this non noble metal containing composite material to have applications in bioimaging and bio and chemical detection. Abstract : The SERS of trititanate nanotubes modified with enediol ligands was found to be dramatically affected by the functional group. When 4‐nitrocatechol is attached an enhancement is seen; however, when dopamine is attached, no signal is seen. The relative band gap positions upon 785 nm laser excitation are proposed to explain the observed phenomenon